Excellent electrical properties and high Curie temperature of the V2O5-modified Pb(Sc1/2Nb1/2)O3–Pb(Mg1/3Nb2/3)O3–PbTiO3 ferroelectric crystal. Issue 28 (28th June 2022) - Lei, Jie; Li, Xiaojuan; Fan, Xing; Yan, Zhaozhong; He, Aiguo; Long, Wei; Fang, Pinyang; Guo, Feifei; Xi, Zengzhe
Abstract : The V2 O5 -doped ternary Pb(Sc1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (V–PSN–PMN–PT) relaxor ferroelectric crystals show excellent piezoelectricity d 33 ≈ 1600 pC/N and high Curie temperature T C ≈ 174 °C. Abstract : In order to overcome the shortcomings, namely, low coercive field ( E C < 3 kV cm −1 ) and low Curie temperature ( T C < 150 °C), of binary Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 relaxor ferroelectric crystals with a morphotropic phase boundary (MPB) composition, we successfully grew V2 O5 -doped ternary Pb(Sc1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (V–PSN–PMN–PT) relaxor ferroelectric crystals with high piezoelectric coefficient d 33 ≈ 1600 pC/N, high Curie temperature T C ≈ 174 °C, large coercive field E C ≈ 7.5 kV cm −1, and large strain S ≈ 0.42% at 3 kV mm −1, which indicates the potential application of V–PSN–PMN–PT crystals in large power transducers and high temperature field. We characterized the phase structure of the V–PSN–PMN–PT crystals and the chemical valence of different elements by using Rietveld structure refinement and X-ray photoelectron spectroscopy to determine that the excellent performances arise from the large lattice distortion and coexistence of monoclinic and tetragonal phases.